THU0661 Clinical relevance of detecting anti-adalimumab antibodies with a drug-tolerant assay. (15th June 2017) - Martinez-Feito, A; Gallego, LY Bravo; Hernandez-Breijo, B; Plasencia, C; Jochems, A; Gonzalez, MA; Monjo, I; Peiteado, D; Bonilla, G; Nozal, P; Balsa, A; Pascual-Salcedo, D
Abstract : Background: Adalimumab (Ada) has proven effective in treating rheumatoid arthritis (RA) and spondyloarthropathies (SpA), although approximately 30% of responders will present secondary clinical failure. Immunocomplex formation between antibodies to Ada (ATA) and Ada can increase drug clearance. Most of the assays to measure ATA present drug interference. Currently, different assays are available to measure total ATA (free and complexed). Objectives: To compare the detection of ATA along Ada treatment between two assays: one drug-sensitive and another drug-tolerant assay. Study the association of ATA with the clinical status. Methods: This is a prospective observational study with 63 patients with rheumatic diseases under Ada treatment enrolled at Biological Therapy Unit of Hospital La Paz. Serum Ada levels were measured by ELISA and serum ATA levels by two assays: an in-house two-site (bridging) ELISA (bELISA) to detect uncomplexed ATA (free ATA) and a drug-tolerant assay developed by ImmundiagnostikÒ (Bensheim, Germany) (IDK) to measure simultaneously free and complexed ATA (total ATA). Samples were evaluated at 0, 0.2, 0.5, 1, 1.5 and 2 years after Ada initiation. Results: Out of the 63 studied patients, 12 (19%) had RA and the rest (51, 81%) had different spondyloarthropathies (24, 38%) ankylosing spondylitis, 9 (14%) psoriatic arthritis, 14 (22%) undifferentiated spondyloarthritis and 4 (6%) spondyloarthritis associated with inflammatory bowel disease).Thirty-one patients (49%) received concomitant methotrexate (26% RA patients and 74% SpA patients), 13 (21%) received another DMARDs associated to Ada and 19 (30%) were on monotherapy.Out of the 63 patients, in 27 (43%) no ATA were detected. Thirty six patients (57%), were IDK+ and 12 patients (19%) were bELISA+ (all of them IDK+).The presence of ATA by bELISA was associated with absence of serum Ada levels. However, most (78%) samples with complexed ATA had low circulating Ada levels (1.65 mg/ml in ATA+ vs 6.25 mg/ml in ATA-, p<0.0001). ATA appeared by IDK at earlier treatment stages than by bELISA, statistically different at all studied time points.In patients who dropped-out (30 patients, 48%) ATA detection was frequent and significant by both methods.Ten patients (33%) bELISA ATA+ dropped-out vs 2 patients bELISA ATA+ in those who continued treatment (p<0.0001). Twenty four patients (80%) IDK ATA+ dropped-out vs 12 patients (36%) who continued treatment (p<0.0001). The percentage of ATA detected by IDK was higher than by bELISA, with a tendency of more IDK ATA+ among patients with less survival (24, 80% IDK positive vs 10, 33% bELISA +; p=0.06) Conclusions: ATA are detected by a drug-tolerant assay at earlier stages of treatment than by bELISA. The antibodies formed early are associated with lower levels of circulating Ada, indicating higher drug clearance. This information might be useful to implement the Therapeutic Drug Monitoring. However, the detection of early complexed ATA has not demonstrated a significant advantage over the bELISA to predict treatment survival. Acknowledgements: This work has been supported by a collaboration with Leti laboratories. Disclosure of Interest: None declared